2020
DOI: 10.4103/joacp.joacp_104_19
|View full text |Cite
|
Sign up to set email alerts
|

Does an acute pain service improve the perception of postoperative pain management in patients undergoing lower limb surgery? A prospective controlled non-randomized study

Abstract: Background and Aim: An acute pain service (APS) has been running in our institute since April 2013 and is managed by the Department of Anesthesia and Intensive Care. However, it is not clear to what extent the patients feel benefited from the APS. The aim of the study was to compare the perception of postoperative pain management in patients receiving care under APS with those receiving routine postoperative pain relief following lower limb surgery. Material and Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
(42 reference statements)
0
6
0
Order By: Relevance
“…If usual surgical recovery is inhibited by unsuccessful functional pain management and/or unacceptable adverse effects despite appropriate multimodal therapies and patient-specific opioid optimization, postoperative pain management specialty consultation is advised. Acute and transitional pain services for surgical patients are evolving, and have been associated with reduced opioid use and length of stay [113,[436][437][438][439][440][441]. Renal impairment increases exposure 1 All listed opioids should be reduced in cases of significant hepatic impairment.…”
Section: Postoperative Opioid Considerationsmentioning
confidence: 99%
“…If usual surgical recovery is inhibited by unsuccessful functional pain management and/or unacceptable adverse effects despite appropriate multimodal therapies and patient-specific opioid optimization, postoperative pain management specialty consultation is advised. Acute and transitional pain services for surgical patients are evolving, and have been associated with reduced opioid use and length of stay [113,[436][437][438][439][440][441]. Renal impairment increases exposure 1 All listed opioids should be reduced in cases of significant hepatic impairment.…”
Section: Postoperative Opioid Considerationsmentioning
confidence: 99%
“…For instance, Lee et al (Lee et al 2010 ) found that the level of pain in rest was lower among patients, cared for by APS, while according to Gould et al (Gould et al 1992 ) pain scores measured with the visual analog scale decreased remarkably after the introduction of APS at general surgery wards. More recently published studies also confirmed that the intensity of postoperative pain among surgical patients decreased after the introduction of any type of APS (Miaskowski et al 1999 ; Mitra et al 2020 ; Fang et al 2021 ). Regarding the impact of pain on physical mobility, Mitra et al (Mitra et al 2020 ) found that pain limited the everyday activities significantly more of patients who were treated by an APS.…”
Section: Discussionmentioning
confidence: 73%
“…More recently published studies also confirmed that the intensity of postoperative pain among surgical patients decreased after the introduction of any type of APS (Miaskowski et al 1999 ; Mitra et al 2020 ; Fang et al 2021 ). Regarding the impact of pain on physical mobility, Mitra et al (Mitra et al 2020 ) found that pain limited the everyday activities significantly more of patients who were treated by an APS. Several studies agree that patients cared for by APS could expect better outcomes, such as more effective pain relief, greater satisfaction, and less opioid consumption (Miaskowski et al 1999 ; van Boekel et al 2015 ; Said et al 2018 , Webb & Kim 2018 ), and the same applies to pain-induced negative emotions (Mitra et al 2020 ).…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations